Exploring the Effects of Imidacloprid on Liver Health and the Microbiome in Rats: A Comprehensive Study - Alaa T. Qumsani (Microorganisms)
The current study investigates the systemic effects of imidacloprid, one of the most widely used neonicotinoid insecticides, on the liver and gut microbiome of rats in detail. With consideration of recent discussions on the potential harmfulness of imidacloprid to environmental and human health, the aim was to investigate the influence of this compound in the framework of controlled exposure at different dosages, namely, IMI-5, IMI-10, and IMI-30. Histopathological examination showed that liver morphology changed significantly with the dose, including in terms of cellular disorganization and signs of stress, with an alteration in the hepatic architecture. Morphological changes were related to disturbances in the activity of liver enzymes, reflecting deteriorating liver function with increased imidacloprid exposure. In parallel with this, a deep analysis of the gut microbiome revealed dramatic changes in microbial diversity and composition. Alpha diversity, represented by the Chao1 and Shannon indices, was significantly reduced with an increased dosage of imidacloprid. Subsequent beta diversity analysis, as visualized by principal component analysis, showed distinct clustering among the microbial communities, separated well between control and imidacloprid-treated groups, especially at higher dosages. Taxonomic analysis revealed an increase in the Firmicutes/Bacteroidetes ratio and a change in key phyla including Actinobacteria, Bacteroidetes, and Verrucomicrobia. A heatmap and bar charts further confirmed dose-dependent changes in microbial abundance. These changes point toward imidacloprid-induced dysbiosis, a reduction in microbial diversity, and an imbalance in the F/B ratio, usually associated with metabolic disorders. Overall, given these findings, it would seem that imidacloprid does indeed impose serious negative impacts on both liver function and gut microbiota composition and may have further impacts on health and ecological safety.